2006
DOI: 10.1183/09031936.06.00110205
|View full text |Cite
|
Sign up to set email alerts
|

Use of a T-cell-based test for detection of tuberculosis infection among immunocompromised patients

Abstract: The aim of this study was to compare the performance of the T-SPOT.TB TM test, a Tcell-based test, with the tuberculin skin test (TST) in the diagnosis of latent tuberculosis (TB) infection.The study was carried out in 138 immunosuppressed haematology patients who had been nosocomially exposed to a case of smear-positive TB.Overall, 44.2% of the contacts were positive by T-SPOT.TB TM test, and 17.4% by TST (concordance 67.8%). The apparent prevalence of infection fell from 25.9 to 14.5% with the TST with incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
12

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 20 publications
4
47
0
12
Order By: Relevance
“…To our knowledge, this is the largest study about the utility of the T-SPOT.TB among hematological malignancy patients and hematopoietic stem cell transplant recipients for detection of tuberculosis infection (Piana et al, 2006;Moon et al, 2013). Patients with hematological malignancy and receiving hematopoietic stem cell transplantation are both high-risk patients to get tuberculosis infection.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the largest study about the utility of the T-SPOT.TB among hematological malignancy patients and hematopoietic stem cell transplant recipients for detection of tuberculosis infection (Piana et al, 2006;Moon et al, 2013). Patients with hematological malignancy and receiving hematopoietic stem cell transplantation are both high-risk patients to get tuberculosis infection.…”
Section: Discussionmentioning
confidence: 99%
“…These tests with positive and nil internal controls are more specific than TST in diagnosing TB infection [3][4][5] and equally or more sensitive in patients with immune deficiencies. Nevertheless, indeterminate results have been reported for both tests with a frequency of 0-5.4% for the T-SPOT TM .TB test [6][7][8][9][10][11] and ,40% for the QuantiFERON1-TB Gold test [12][13][14][15][16][17]. Their occurrence seems to be associated with immunosuppression [10,18] and very young or very old age (patients aged ,5 or .80 yrs).…”
mentioning
confidence: 99%
“…In terms of sensitivity, there are several studies that showed that the IGRAs are more sensitive than the TST. 15,102,103,106 Ponce de Leon et al 15 recently showed that, in a population from an endemic area for TB, the ELISPOT was significantly more sensitive than the TST for diagnosis of latent TB in patients with rheumatoid arthritis, but the same result was not found in healthy patients. Such finding probably was associated with immunosuppression of the disease and/or medication used in the disease treatment.…”
Section: Elispot (Available In the Market As T-spottb ® Oxfordmentioning
confidence: 78%
“…[98][99][100] Ferrara et al 79 found high rate of undetermined results Other studies have shown that the prevalence of positive ELISPOT results was higher than that found using the TST, mainly in immunosuppressed patients. 16,102,103 79 suggested that IGRAs specificity is higher than TST specificity for the diagnosis of tuberculosis infection.…”
Section: Elispot (Available In the Market As T-spottb ® Oxfordmentioning
confidence: 99%